GROWTH PERFORMANCE, TIBIAL BONE MORPHOMETRICS, COPPER AND ZINC STATUS IN ASEEL CHICKEN UNDER DIFFERENT SYSTEMS OF REARING – A FIELD STUDY - Murali Pitchandi (Journal of Animal and Plant Sciences, 2026)
The present study was conducted to evaluate the growth performance, bone morphometrics, copper and zinc profile of body tissues in Aseel chicken reared under different systems of rearing. A total of 72 Aseel birds were selected at marketing age from 18 farms, of which 24 birds each from intensive (3 months), semi-intensive (6 months) and backyard system (9 months) of rearing. Feed and water samples from each farm were collected to assess the copper and zinc levels. The selected birds were weighed and slaughtered to collect bone and liver samples for copper and zinc analysis. The data collected were analyzed following completely randomized design. copper and zinc levels in feed and water to birds in intensive system, semi-intensive system and backyard system of rearing were 27.39, 15.16, 7.41 and 147.33, 84.19, 28.98 ppm and 0.92, 0.48, 0.49 and 1.07, 0.97, 0.72 ppm, respectively. The body weight of birds (both male and female) was significantly (P<0.01) higher in the intensive system as compared to semi-intensive and backyard system of rearing. Tibial bone length, bone weight and seedor index were significantly (P<0.05) higher in birds reared under intensive and semi-intensive systems, whereas no significant difference was noticed in robursity index, circumference and relative bone weight among the birds reared under different systems. Both zinc and copper content of liver and bone were significantly (P<0.01) higher in the birds grown under intensive system of rearing when compared to semi-intensive and backyard system of rearing. The present study revealed that the growth performance, bone morphometric indices, copper and zinc status in liver and tibial bone were significantly higher in Aseel birds grown under intensive system as compared to semi-intensive and backyard system which might be due to feeding with a concentrate feed containing higher (27.39 ppm copper and 147.33 ppm zinc) levels of these minerals.
Keywords: Aseel chicken; growth performance; system of rearing; copper and zinc status